Let me show you an example problem.

If two people averaged 15 years old, how old are they added together?

remember, the average is:average=(the sum of all tries)/(the number of tries)

substitute:15=(The sum of all tries)/2

multiply both sides by two to get:30=The sum of all tries

but what if someone messed up and one of the people's ages were 4 years older, what would be the mean then?

We know that the sum is already 30, so all we need to do is add 4 on and find the new mean, so:

Average=(The sum of all tries)/(the number of tries)

substitute:Average=34/2

divide:Average=17

Can you do your problem now?